Congenital brucellosis: A case report. Issue 12 (December 2020) - Mohzari, Yahya Ali; Alshuraim, Renad Abdullah; Asdaq, Syed Mohammed Basheeruddin; ALanazi, Saud O.; Alghamdi, Najwa; Alrashed, Ahmed A.; Hassounhe, Amal Khalil; Alzaaqi, Meshal A.
Although rare, brucellosis is endemic in the Kingdom of Saudi Arabia (KSA). In the case presented here, a neonate was born at 29 weeks gestation with severe respiratory depression, pyrexia; hypotension and an elevated white blood cell count. Her mother was a 19-year-old pregnant woman who developed premature rupture of the membranes and went into labour early. Sepsis was suspected and so the neonate received dobutamine and empiric ampicillin/gentamicin. The mother reported visiting a farm during her pregnancy and so congenital brucellosis was considered a possibility. Blood cultures were positive for Gram-negative coccobacilli and serology confirmed the presence of Brucella abortus and B. meltiness. Antibiotic treatment was changed to rifampin/gentamicin/ciprofloxacin but on day 17 the baby deteriorated and gentamicin was discontinued and meropenem was added. The neonate gradually improved; meropenem was discontinued on day 24 and the baby was discharged from hospital on day 38.